NEW REPORT OF DECAPOD AND ISOPOD CRUSTACEANS FROM THE LOWERMIDDLE PLEISTOCENE OF MONTALBANO JONICO, MATERA (BASILICATA, SOUTHERN ITALY) - Angela Girone; ALESSANDRO GARASSINO; GIOVANNI PASINI; ANDREA ZAZZERA; SALVATORE GALLICCHIO; PATRIZIA MAIORANO; MARIA MARINO; RAFAEL LA PERNA (Rivista Italiana di Paleontologia e Stratigrafia, 2024)
The study of the Lower-Middle Pleistocene decapod crustacean fauna from Montalbano Jonico succession allowed 12 taxa to be recognized. The studied samples include some fossil species already known from the Pleistocene record of Italy, as Ebalia nux A. Milne-Edwards, 1883, Monodaeus bortolottii Delle Cave, 1988, Liocarcinus depurator (Linnaeus, 1758), Goneplax rhomboides (Linnaeus, 1758), and Chlinocephalus demissifrons Ristori, 1886. These species are reported for the first time from Basilicata, except for E. nux, whereas Carcinoplax jonica n. sp. and Neogoneplax bradanica n. sp. are introduced as new species. Moreover, one poorly preserved specimen is assigned to Ebalia sp.; one dubitative specimen to ?Carcinus sp.; one specimen to Bathycalliax sp. (Axiidea de Saint Laurent, 1979); one to an indeterminate galatheid; and two poorly preserved large-sized specimens are tentatively referred to Carcinoplax sp. (Goneplacidae, MacLeay, 1838). Finally, several indeterminate specimens of cirolanid (Isopoda) are reported, as well. The studied decapod community from Basilicata allows us to expand our knowledge of Pleistocene fossil crabs and their distribution around the Mediterranean Sea basin in the Lower-Middle Pleistocene.